Model Inovasi Wisata Wellness dan Gastronomi Berbasis Penghidupan Lestari di Kawasan Pantai Pangandaran - Rizky, Fahmi Muhamad; Bahreisy, Afghani Mahmuda; Gumilang, Muhamad Akbar (Politeknik Pariwisata NHI Bandung, 2025)
The innovative tourism model based on wellness and gastronomy through the Sustainable Livelihood Approach (SLA) in the Pangandaran coastal area is designed as a strategy for inclusive and sustainable tourism development. This model addresses the challenges of mass tourism, such as overcapacity, environmental degradation, and unequal distribution of economic benefits. By integrating dimensions of health, local culture, and community empowerment, this approach positions tourism as a tool for poverty alleviation, environmental preservation, and social transformation. This study employs a qualitative method with an exploratory-conceptual approach, through literature review and participatory observation. The findings reveal that the combination of wellness and gastronomy can encourage economic diversification, create decent employment, strengthen local identity, and reduce pressure on coastal ecosystems. This model has proven to support the achievement of the Sustainable Development Goals (SDGs), particularly Goals 1, 3, 8, 12, 14, 15, and 17. The involvement of nine stakeholders through the nona-helix framework strengthens cross-sector collaboration in realizing systemic destination transformation. This study offers a conceptual contribution to community-based destination development and recommends replicating similar models in other coastal tourism areas in Indonesia.